Evaluation of a pineapple solar drying system using bentonite, charcoal and rice, separately, as desiccants for air drying (Research, Society and Development, 2022)
The present work aims to evaluate a low cost direct exposure solar drying system, easy to operate, accessible to family farmers and of high efficiency that uses desiccant for drying air in the city of Campina Grande - PB. The methodology used consisted in the construction of two dryers of identical characteristics and dimensions, which, when experimentally tested, one of them was (integrated) to a desiccant unit (desiccant chamber) while the other was without a chamber. The outlet temperatures obtained in the dryers with and without desiccant chambers were close, different from the value of the relative humidity of the air. The average relative humidity of the drying air recorded was approximately 16.8% in the dryer with desiccant, while in the dryer without desiccant the average was approximately 17.6%. The collected data allowed the realization of the energy balance of the solar dryer, resulting in the calculation of the thermodynamic efficiency of the solar dryers, which was on average 38.89% for the dryers with desiccant and 36.93% for the dryer without desiccant. The average mass efficiency of the drying process was around 99% for the dryer with desiccant and 98% for the dryer without desiccant. Finally, it was possible to conclude that the use of desiccant materials can help to improve the thermal performance of an equipment, and that bentonite was the most efficient desiccant compared to charcoal and rice.